BIOM-36. THE UNIQUE METABOLOMICS BASED BIOMARKERS OF RESPONSE TO IMMUNOTHERAPY FOR GLIOBLASTOMA. (9th November 2020) - Dastmalchi, Farhad; Karachi, Aida; Mehkri, Yusuf; Khattri, Ram; Merritt, Matthew; Kubilis, Paul; Mitchell, Duane; Rahman, Maryam
Abstract: INTRODUCTION: The adaptive immune response requires robust T cell proliferation and activation. These T cell changes are dependent on metabolic program shifts that can be measured using metabolomic analysis. The objective of this project was to identify a metabolomics profile to serve as a biomarker of response to immunotherapy for the treatment of brain tumors. METHODS: GL261-gp100 tumor-bearing mice were received anti-PD1 or bone marrow-derived dendritic cell (DC) vaccine that was generated ex vivo. Urine samples were collected for Nuclear Magnetic Resonance (NMR) analysis. A more in-depth Sparse Partial Least Squares Discriminant Analysis (sPLS-DA) revealed global metabolic changes induced with immunotherapy. RESULTS: The metabolic changes were most dramatic at 24 hours post DC vaccination and slowly returned to baseline at 7 days post DC vaccination. The main drivers of the differences included creatine, n-dimethyl glycine, alanine, lactate, glucose, glutamine, leucine, citrate and formate. Anti-PD1 therapy-related metabolic changes were largest around day 20 post therapy and the main drivers of the differences included dimethyl sulfone, succinate, lactate and isobutyrate. CONCLUSION: Immunotherapy results in systemic metabolic changes that serve as a biomarker treatment effect. These findings have translational relevance in predicting patients who will develop an immune response to immunotherapy and ultimately have better outcomes with treatment.